2016
DOI: 10.1590/1415-4714.2016v19n2p322.10
|View full text |Cite
|
Sign up to set email alerts
|

O exame de Verificação de Cessação de Periculosidade: a importância da avaliação ampliada em um caso com conclusão contrária ao parecer da equipe assistente

Abstract: Trata-se de uma discussão a respeito de um caso em que um indivíduo sob medida de segurança, devido a tentativa de homicídio, foi submetido à avaliação de sua periculosidade por peritos psiquiatras. A conclusão foi de que sua periculosidade não havia cessado, divergindo da opinião de sua equipe assistente. Foram identificados relevantes fatores que implicam um maior risco de violência e reincidência criminal, demonstrados no laudo. O resultado mostra que uma avaliação criteriosa e independente é fundamental pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The presumed dangerousness only ends with the Examination to Attest the Cessation of Dangerousness, which must be carried out by an official expert psychiatrist. Mecler (2010) and Oliveira et al (2016) researched hundreds of Brazilian psychiatric reports and identified that, in most of these exams, the psychiatric expert does not seem to subject his report to a standardization and systematization that takes the most relevant points in the risk of violence into consideration, in disagreement with what is presented in the scientific literature comprised in this review.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The presumed dangerousness only ends with the Examination to Attest the Cessation of Dangerousness, which must be carried out by an official expert psychiatrist. Mecler (2010) and Oliveira et al (2016) researched hundreds of Brazilian psychiatric reports and identified that, in most of these exams, the psychiatric expert does not seem to subject his report to a standardization and systematization that takes the most relevant points in the risk of violence into consideration, in disagreement with what is presented in the scientific literature comprised in this review.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have sought to associate the risk of violence with mental health disorders, but many have described small or specific samples, such as populations exclusively selected from custody hospitals or even prisons, resulting in an inadequate analysis of the mental health disorders themselves (Adshead, 1998;Flannery Junior et al, 2000;Kramp;Gabrielsen, 2009;Moscatello, 2001;Oliveira et al, 2017;Short et al, 2013). On the other hand, there are other studies demonstrating relations contrary to this (Fazel;Yu, 2011;Ghoreishi et al, 2015;Mecler, 2010;Oliveira et al, 2016). Violence in individuals with mental disorders can be certainly prevented through psychiatric treatment and clinical management regarding this aspect (Valença et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…There is no correct answer or definitive solution for these individuals, but the presence of psychopathy or PCL‐R typical items are relevant, which must necessarily be considered in the forensic psychiatry evaluation. Psychopathy should directly interfere with criminal responsibility and according to Abdalla‐Filho (Oliveira et al., 2016), there is a lack of consensus among experts in this aspect, if there is a diagnosis of personality disorder, especially with regard to the antisocial group or specifically the psychopath. One possible solution would be to provide separate living spaces for psychopaths and individuals with major mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…There are few citations in the reports of items related to the severity of the crime, criminal history, and even psychiatric history. Such items are crucial in violence risk assessments (Nicholls et al., 2013; Oliveira et al., 2016; Webster et al., 1997; Whittington et al., 2013). It is appropriate to reflect that historical items are static and immutable and, hence, dynamic items should be prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…For this, the type of population and sampling used, as well as the method of translation and validation of the instrument for the research, were analyzed. The study using the Historical, Clinical, Risk Management -20 (HCR-20), for example, assessed only one individual case, describing an examination conducted for the Cessation of Dangerousness Assessment in the context of the Brazilian Penal Code which, in its essence, dates back to 1940 (Oliveira et al, 2016). The authors carried out an exploratory study using this instrument, which has versions in English, addressing its validation in Brazil (Telles et al, 2009).…”
Section: ) In Which Population Have These Tests Been Validated To Pro...mentioning
confidence: 99%